Gaya Bahasa Repetisi Epizeuksis dalam Cerpen Ciung Pulang! Karya Asha Ray - Diana, Jumianti; Nurmalasari, Nurmalasari (Universitas Negeri Padang, 2025)
This research aims to present information about epizeuxis repetition style of language found in short stories entitled Ciung Pulang! Asha Ray’s work. The research methods used is qualitative research. Data collection was carried out by listening method with note taking technique. The data found will be analyzed and described. The research results show that there is epizeuxis repetition which describes the atmosphere of the night which is full of tension is increasingly disturbed by the shouting of the word Ciung, create a strong emotional impression, describes a longing or urgent desire for together, describes the importance of the character Amak for the character Apak, shows emotional intensity in his invitation to come home. Epizeuxis repetition contained in that short story emphasize feelings of anxiety or very deeps concern, and create great attention.